From Education to Practice: The Impact of Health Informatics, Nursing, Health Administration, Laboratory Sciences, Clinical Education, and Training Management on Advancing Healthcare in Saudi Arabia - Hasna Radhi Muharab Al Shammari; Jamailh Suleiman Ali Al-Aida; Maha Radhi Muharab Al Shamri; Tahani Abdullah Sadun Almayzar; Ali Mhna’a Alshamari; Aisha Abdullah Hamoud Al-kharin; Fatimah Musaad Owdah Almosi Alhwiti; Hasna Awadh Bulayzana Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Saudi Arabia is going through a transformative phase in health care such as its Vision 2030, where it concentrates its energies on building a sustainable quality health care delivery system. Moving the country from an oil-dependent economy to a diversified one, health has focused itself intensively in investments and innovations. Furthermore and foremost, the advanced education and practice in areas like health informatics, nursing, health administration, laboratory sciences, clinical education, and the management of training programs are where the 21st-century revolution is taking place. These disciplines together forms backbone of modern healthcare delivery by improving efficiency, patient outcomes as well as ensuring that the workforce is ready to face emerging challenges. Aim of work: Toexplore the critical contributions of Health Informatics, Nursing, Health Administration, Laboratory Sciences, Clinical Education, and Training Management on the ongoing transformation of healthcare in Saudi Arabia. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Impact, Health Informatics, Nursing, Health Administration, Laboratory Sciences, Clinical Education, Training Management, Advancing, Healthcare, Saudi Arabia. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Saudi Arabia is spearheading advancement in its healthcare system through well-defined integration of the health informatics sciences, nursing, health administration, laboratory sciences, clinical education, and training management. The above mentions contribute to a complete and functional construct regarding dealing with the needs of a diversely populated society. Hence those areas being quite important for the future success of the health system in Saudi Arabia within the Vision 2030 initiative purposes an icing cooperation among them to affect the lives of individuals in a longer term. In the patient care optimization phase, health informatics contributes; while nursing takes leadership roles in health administration on the one hand by formulating policies that govern precision medicine efficiency in laboratory sciences as clinical education prepares professionals in facing the real-world challenges, while training management upholds a skilled workforce.